Lietuvos proistorė ir Lietuvos istorija: lūžio problematika - Kuncevičius , Albinas; Luchtanas, Aleksiejus (Lietuvos istorijos studijos, 1997)
• In the broad sense, prehistory and history are two major and complementary components of a unified approach to historical research. • Current Lithuanian archaeological periodization, especially the second half of the first millennium after Christ and into the beginning of the second millennium, does not reflect the dynamic process of prehistory. • The major break in Lithuanian social and economic development, which is clearly indicated in the archaeological material culture, took place not in the 9th century, as stated in the traditional literature, but at the end of the 10th century and through the 11th century. This was the eve of the formation of the feudal Lithuanian state. Archaeological and historical sources allow us to follow common historical processes, and this should reflect the periodization of prehistory.